Superconducting phase-dependent force in SNS junctions with a movable scatterer - Parafilo, A.V.; Krive, I.V.; Bogachek, E.N.; Landman, U. (Физика низких температур, 2012)
We calculate a quantum (Casimir-like) superconducting phase-dependent force acting on a movable scatterer in a superconductor–normal metal–superconductor (SNS) junction. Repulsive Casimir forces are predicted for a short SNS junction with nonequilibrium (inverse) populations of Andreev levels. In a long SNS junction an anomalous (nonmonotonic) temperature behavior of quantum force is found.